Novel investigations in retinoic-acid-induced cleft palate about the gut microbiome of pregnant mice - Wang, Yijia; Chen, Jing; Wang, Xiaotong; Guo, Cui; Peng, Xia; Liu, Ying; Li, Tianli; Du, Juan (Frontiers in Cellular and Infection Microbiology, 2022)
Cleft palate (CP) is one of the most common congenital birth defects in the craniofacial region, retinoic acid (RA) gavage is the most common method for inducing cleft palate model. Although several mechanisms have been proposed to illuminate RA-induced cleft palate during embryonic development, these findings are far from enough. Much efforts remain to be devoted to study the etiology and pathogenesis of cleft palate. Current research is gradually shifting the focus to the effect of retinoic acid on gut microbiota. However, few reports focus on the relationship between the occurrence of CP on embryos and gut microbiota. In this study, we used RA to induce cleft palate model for E10.5 mice, then on E16.5, the feces of 5 RA-treated pregnant mice and 5 control pregnant mice were respectively collected for metagenomics analysis. The results showed that compared with the control group, Lactobacillus in the gut microbiome of pregnant mice in the RA group was significantly increased. GO, KEGG and CAZy analysis of differentially expressed unigenes demonstrated the most abundant metabolic pathway in different groups, such as TCA cycle, lipopolysaccharide biosynthesis, and histidine metabolism. Our findings indicated that changes in maternal gut microbiome could affect fetal palatal development, which might be related to changes in Lactobacillus and metabolic disorders. These results provide a new direction in the pathogenesis of CP induced by RA.